Penerapan Metode Fuzzy Tsukamoto Dalam Memprediksi Permintaan Barang - Dwi Melina; Diana Diana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Azthana Digital Media is a digital agency that works with a number of Indonesian vendors, including Pempek Mola, Pempek Kalani, and Eightsy Bag. Azthana oversees distribution and maintains warehousing for all three brands simultaneously. However, due to fluctuations in product demand, there are sometimes gaps in the supply of goods across all brands. So we need a method that can be implemented in inventory management and product development in the future. Forecasting strategies are useful tools for maintaining and expanding stock levels. In this study, researchers used the Fuzzy Tsukamoto technique built into a web-based inventory system to estimate consumer demand. Sales data, product purchases and goods production data are the three main inputs used to formulate demand forecasts. The results of this study can be concluded that the inventory system created can help the related team to find out the exact amount of stock available and to implement the Tsukamoto fuzzy calculations in predicting the demand for goods in the system that is running well as evidenced by the results of manual calculations and the system if the demand value is input equal to 355 with four fuzzy rules that are set together to produce a production value of requests for goods that must be ordered to suppliers of 522 packs.